Literature Review: Hubungan Melewatkan Sarapan dengan Overweight/Obesitas - Arum, Ristanti Sekar; Sumarmi, Sri (Universitas Airlangga, 2024)
Background: The number of overweight and obese people in the world is increasing, and the worldwide increase in obesity affects health and reduces quality of life. Obesity is a risk factor for degenerative diseases that have serious health consequences. Research conducted in 2016 showed that more than 1.9 billion adults aged 18 years and older are overweight. Factors that influence the occurrence of obesity are genetics, less physical activity, more calorie intake, and an irregular diet. Objectives: This study aimed to determine the association between skipping breakfast and overweight/obesity. Methods: The writing of this review article used a literature review approach where this study used data findings and/or previous research data on the topic of skipping breakfast with overweight / obesity in as many as six cross-sectional studies, case-control and cohort. The databases used are Science Direct, Scopus, and PubMed. Results: Regular breakfast can effectively reduce the risk of obesity. Skipping breakfast can change the circadian rhythm, which is the natural pattern the human body repeats every 24 hours, which can affect energy intake, bodily functions and emotional states. These changes can cause a person to consume more calories during the day and night, resulting in an increase in body fat, which manifests as weight gain. Changes in eating habits impact fast food consumption, which will increase total energy consumption. Conclusions: Based on the six articles reviewed, all articles showed a significant association between skipping breakfast and obesity. Five studies showed significant results that gender was one of the influences on the association of breakfast skipping with obesity. Still, there was no dietary assessment in the reviewed studies, including energy and nutrient energy and nutrient consumption data to assess the distribution of daily intake between meals. However, one another article shows no association of gender with meal skipping.